2021
DOI: 10.3389/fpsyg.2021.632134
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Online Psychological Intervention on Burnout in Medical Residents From Different Majors: An Exploratory Study

Abstract: Background: Work-related stress among healthcare professionals poses a serious economic and healthcare burden. This study aimed to investigate the prevalence of burnout as well as anxiety, depression, and stress in medical residents from different majors, and assess the effects of an online psychological intervention on the mental health status of medical residents with a high degree of burnout.Methods: We conducted an online survey that collected information on the demographics, mental health, and burnout con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(10 citation statements)
references
References 25 publications
0
10
0
Order By: Relevance
“…Therefore, burdened physicians are informed about effective and feasible interventions provided to help them improve their well-being. Moreover, online interventions are easily accessible, user friendly, and less time consuming [30]. This review also stresses the importance of the sustained effect of the selected PIMs.…”
Section: Aim and Research Questionsmentioning
confidence: 95%
“…Therefore, burdened physicians are informed about effective and feasible interventions provided to help them improve their well-being. Moreover, online interventions are easily accessible, user friendly, and less time consuming [30]. This review also stresses the importance of the sustained effect of the selected PIMs.…”
Section: Aim and Research Questionsmentioning
confidence: 95%
“…Depressive symptomatology was assessed in 7 studies; 3 interventions produced significant reductions posttreatment: the guided Sudarshan Kriya Yoga workshop (Divya et al, 2021), the online self‐compassion cultivation program (Finlay‐Jones et al, 2017), and the mindfulness decompression and psychoeducation program (Wang et al, 2021). None of these studies was compared to control conditions; Smoktunowicz et al (2021) did compare different versions of the Med‐Stress program but found no differential effects on depression.…”
Section: Resultsmentioning
confidence: 99%
“…The impact of the intervention on burnout levels was reported in 7 of the studies reviewed. Five of them observed significant reductions in this outcome: web‐based ACT and web‐based CBT (Barrett & Stewart, 2021), and the mindfulness decompression and psychoeducation program (Wang et al, 2021) produced significant reductions posttreatment; also, the study conducted by Osman et al (2021) reported effects on the emotional exhaustion and personal accomplishment facets of burnout, but not on depersonalization. Moreover, the mindful and self‐compassion program (Eriksson et al, 2018) and the guided session teaching emotional freedom techniques (Dincer & Inangil, 2021) produced significant improvements in burnout compared to control groups.…”
Section: Resultsmentioning
confidence: 99%
“…Those who used the app during stage 2 completed <2 skill activities on average despite “liking” most activities completed. Although the observed pattern of disengagement over time is common for digital and app-based psychological interventions [ 30 , 78 ], it is incongruent with the fact that students who completed the introductory module generally reported that they would like to use the app in the future. These findings reinforce the need for a detailed formal evaluation of end-user experiences to better understand factors that may affect feasibility [ 1 ] and guide app intervention development, which was the second aim of this study.…”
Section: Discussionmentioning
confidence: 99%